2008
DOI: 10.1080/15476910802131469
|View full text |Cite
|
Sign up to set email alerts
|

The Opioid Antagonist Naltrexone Improves Murine Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD) is a condition of the intestine with significant morbidity. Although hereditary, environmental, immunologic, and bacterial factors have been implicated, the etiology of IBD remains unknown. Since opioid peptides modulate inflammatory cytokine production and opioid antagonists promote tissue growth and repair, we hypothesized the opioid antagonist naltrexone could reduce inflammation of the bowel. Using a chemically-induced mouse model of IBD, C57BL/6J mice received either untre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Interestingly, previous reports have shown that low-dose therapy of the nonspecific opioid antagonist naltrexone protects against both DSS-induced injury in mice and ameliorates Crohn's disease in a small, open-label patient study. 41,42 In these studies, naltrexone was deliberately administered at levels below the dose needed to pharmacologically block receptor function. Because the MOR-specific antagonist cyprodime exacerbates DSS-induced colitis, it is probable that low-dose naltrexone therapy acts to potentiate endogenous opiate signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, previous reports have shown that low-dose therapy of the nonspecific opioid antagonist naltrexone protects against both DSS-induced injury in mice and ameliorates Crohn's disease in a small, open-label patient study. 41,42 In these studies, naltrexone was deliberately administered at levels below the dose needed to pharmacologically block receptor function. Because the MOR-specific antagonist cyprodime exacerbates DSS-induced colitis, it is probable that low-dose naltrexone therapy acts to potentiate endogenous opiate signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Because the MOR-specific antagonist cyprodime exacerbates DSS-induced colitis, it is probable that low-dose naltrexone therapy acts to potentiate endogenous opiate signaling. [41][42][43] However, such a mechanism remains controversial and has never been truly established.…”
Section: Discussionmentioning
confidence: 99%
“…Although few basic science reports have been published, patient studies are provocative. In a murine model of inflammatory bowel disease, low dosages of naltrexone were shown to reduce the weight loss and lessen the disease activity, normally associated with progression of the disorder [85]. The short term opioid receptor blockade reversed the physical symptoms, pathology, and molecular markers of inflammation associated with colitis.…”
Section: Inflammatory Bowel Disease and Fibromyalgiamentioning
confidence: 99%
“…Other autoimmune diseases that respond to partial opioid receptor blockade include the family of inflammatory bowel disorders (Crohn"s and colitis) [82][83][84][85]. Although few basic science reports have been published, patient studies are provocative.…”
Section: Inflammatory Bowel Disease and Fibromyalgiamentioning
confidence: 99%
“…Matters et al [57] reported that naltrexone reduced intestinal inflammation and pro-inflammatory cytokines in dextran sulfate sodium (DSS) model in mice.…”
Section: Smith Et Al [28] Rutgeerts Et Al [44] Jones Et Al [45] Domentioning
confidence: 99%